Strategi Pemasaran Politik Mohammad Idris-Imam Budi Hartono pada Pilkada Serentak Kota Depok Tahun 2020 di Era Pandemi Covid-19 - Zahra, Andi Ulfatul; Armin, Armin; Nadir, Sakinah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Covid-19 pandemic brought multi-sector changes in Indonesia not only in the fields of education and the economy, but also affected the democratic system in Indonesia in the implementation of the simultaneous Pilkada which was planned to be held in September 2020 postponed for up to 3 months. By continuing to carry out the Pilkada it was proven that the organizer, namely the KPU, issued regulations regarding campaigns during the Covid-19 pandemic so as not to trigger new clusters, which in the end made the candidates, including Idris-Imam, consider his marketing strategy so that he could win the contest that took place in Depok City. The aim of this paper is to describe the marketing strategy for the 2020 Depok Mayor and Deputy Mayor elections, this is interesting to review because of its implementation in the Covid-19 era. This study used a qualitative method whose analysis used descriptive data whose data were obtained from informants from the Idris-Imam winning team, members of the social media division and members of the winning team, while also using a number of articles or documents related to this paper. The results of this study indicate that the marketing strategy used by Idris-Imam follows the marketing concept of Nursal (2004): 1) Push Marketing, in marketing Idris-Imam interacts directly with the public from door to door by applying applicable rules, 2) Pull Marketing, the covid-19 pandemic is not an obstacle for Idris-Imam optimizes many social media platforms to disseminate its activities to gain public attention, 3) Pass Marketing, in marketing cooperates with religious figures and influencers to gain support to strengthen Idris-Imam reputation in public.